Repurposing Disulfiram for Cancer Therapy: Mechanistic Insights and Translational Challenges - Anna Bilska-Wilkosz; Magdalena Górny; Małgorzata Iciek (International Journal of Molecular Sciences, 2026)
Disulfiram (DSF), long used as an aversive agent in alcohol dependence therapy, has recently regained attention as a promising candidate for oncological drug repurposing. After administration, DSF is rapidly reduced to diethyldithiocarbamate (DDC), which, in the presence of Cu2+, forms the complex Cu(DDC)2. This compound acts as a strong inducer of oxidative stress, an inhibitor of the ubiquitin–proteasome system, and a suppressor of endogenous hydrogen sulfide (H2S) synthesis. DSF also modifies protein and non-protein thiol groups, disrupting cancer cell metabolism and promoting apoptosis. Despite robust preclinical evidence, clinical translation remains limited. Key obstacles include DSF’s rapid metabolism, insufficient availability of free copper ions in humans, and the lack of predictive biomarkers capable of identifying responsive patients. Another challenge is DSF’s low oral bioavailability, which prevents the drug from reaching tumor tissue at therapeutically effective concentrations. Consequently, current research focuses on advanced nanocarrier systems designed to protect DSF from premature degradation and ensure its controlled release within the tumor microenvironment. This review summarizes the multifaceted anticancer mechanisms of DSF and discusses biological and pharmacological factors underlying the discrepancies between experimental findings and clinical outcomes.